Incidence and Outcomes of COVID-19 in Kidney and Liver Transplant Recipients With HIV: Report From the National HOPE in Action Consortium. Issue 1 (January 2021) - Mehta, Sapna A.; Rana, Meenakshi M.; Motter, Jennifer D.; Small, Catherine B.; Pereira, Marcus R.; Stosor, Valentina; Elias, Nahel; Haydel, Brandy; Florman, Sander; Odim, Jonah; Morsheimer, Megan; Robien, Mark; et al.
Abstract : Background: Transplant recipients with HIV may have worse outcomes with coronavirus disease 2019 (COVID-19) due to impaired T-cell function coupled with immunosuppressive drugs. Alternatively, immunosuppression might reduce inflammatory complications and/or antiretrovirals could be protective. Methods: Prospective reporting of all cases of SARS-CoV-2 infection was required within the HOPE in Action Multicenter Consortium, a cohort of kidney and liver transplant recipients with HIV who have received organs from donors with and without HIV at 32 transplant centers in the United States. Results: Between March 20, 2020 and September 25, 2020, there were 11 COVID-19 cases among 291 kidney and liver recipients with HIV (4%). In those with COVID-19, median age was 59 y, 10 were male, 8 were kidney recipients, and 5 had donors with HIV. A higher proportion of recipients with COVID-19 compared with the overall HOPE in the Action cohort were Hispanic (55% versus 12%) and received transplants in New York City (73% versus 34%, P < 0.05). Most (10/11, 91%) were hospitalized. High-level oxygen support was required in 7 and intensive care in 5; 1 participant opted for palliative care instead of transfer to the intensive care unit. HIV RNA was undetectable in all. Median absolute lymphocyte count was 0.3 × 10 3 cells/μL. Median CD4 pre–COVID-19 was 298 cells/μL, declining to <200 cells/μl in 6/7 with measurements on admission. Treatment included high-dose steroids (n = 6), tocilizumab (n = 3), remdesivir (n = 2), and convalescent plasma (n = 2). Four patients (36%) died. Conclusions: Within a national prospective cohort of kidney and liver transplant recipients with HIV, we report high mortality from COVID-19. Abstract : Supplemental Digital Content is available in the text.